2022
DOI: 10.2174/18742858-v16-e2206030
|View full text |Cite
|
Sign up to set email alerts
|

Sero-Prevalence, Infectivity, and Associated Risk Factors of Hepatitis B Virus Among Pregnant Women Attending Antenatal Care in Sankura Primary Hospital, Silte Zone, Southern Ethiopia, 2021

Abstract: Background: Hepatitis B (HBV) infection causes a major public health problem around the globe. Therefore, this study aimed to assess the Seroprevalence, infectivity, and associated factors of hepatitis B virus infection among pregnant women attending antenatal care in Sankura Primary Hospital, Southern Ethiopia. Methods: A cross-sectional study design was conducted in Sankura Primary Hospital, Southern Ethiopia, from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…Among the various viruses that cause hepatitis, HBV is responsible for both acute and chronic infections. It is the most prevalent and severe liver infection globally, leading to significant morbidity and mortality [ 8 , 9 , 60 ]. However, there is limited documentation regarding the national prevalence of hepatitis B infection among pregnant women.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Among the various viruses that cause hepatitis, HBV is responsible for both acute and chronic infections. It is the most prevalent and severe liver infection globally, leading to significant morbidity and mortality [ 8 , 9 , 60 ]. However, there is limited documentation regarding the national prevalence of hepatitis B infection among pregnant women.…”
Section: Discussionmentioning
confidence: 99%
“…Several medically necessary viruses pose a significant risk to the well-being of millions of people worldwide [ 3 , 4 , 6 ]. Hepatitis B virus (HBV) is a substantial global public health issue [ 7 – 9 ] and belongs to the hepadnavirus family, a group of deoxyribonucleic acid (DNA) viruses [ 2 ]. It primarily affects the liver and can lead to both short-term and long-term health problems [ 8 , 9 ], resulting in significant levels of illness and death [ 7 , 10 14 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…According to our research, participants in the study who had a history of blood transfusions were 14.2 times more likely to be HBsAg seropositive. A related study carried out at the Sankura Primary Hospital in southern Ethiopia showed that the risk of HBV infection increased by 4.8 times [ 34 ]. Another study conducted in Ethiopia also showed that pregnant women with a history of transfusions are 5.71 times more likely to contract HBV [ 35 ].…”
Section: Discussionmentioning
confidence: 99%